The Reception of the Qur'an in Traditional Medical Practice: A Living Qur'an Study of the Therapeutic Dimension of the Qur'an - Rokhman, Mauhibur; Kartiko, Ari; Zamawi, Bahrudin; Maryati, Srikandi (Dirasah International Journal of Islamic Studies, 2025)
This study aims to analyze the practice of using Quranic verses as a medium for healing and to understand its meaning as well as public responses to it. The phenomenon of Quranic verse-based healing represents a form of living reception of the Quran embedded within socio-religious practices. In this context, Quranic verses are not only regarded as sacred texts recited in acts of worship but are also interpreted as therapeutic instruments believed to possess spiritual power in the healing process. This practice is typically carried out by traditional healers known as molang, individuals recognized within the community for their specialized knowledge and experience in utilizing Quranic verses as healing media. Employing a qualitative approach with the Living Quran method, this field research focuses on the functional reception of the Quran within society. Data were collected through interviews, observations, and documentation involving healers and community members who engage with these practices. The analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that healing practices performed by molang, such as Abdullah Marjuki and Ridwan Janan, combine the recitation of Quranic verses with specific media, forming a distinctive model of traditional medicine. These verses are believed to carry spiritual efficacy capable of addressing various illnesses. Strong public trust contributes significantly to the continuity of this practice. Overall, community responses indicate positive perceptions of its effectiveness, enabling this tradition to persist within religious and cultural life.